SISTEM PAKAR KERUSAKAN LAPTOP MENGGUNAKAN METODE BACKWARD CHAINING BERBASIS WEB - Andri Nofiar Am (JSR : Jaringan Sistem Informasi Robotik, 2022)
Laptop is one type of computer that is in great demand by the public at this time, especially for activities such as processing sales data and also purchasing and others can be done using a laptop. In using a laptop, there are several problems that are often faced at this time, namely the damage that occurs to the laptop and how to solve the problem of dealing with the damage to the laptop. Therefore, a web-based laptop damage expert system was created that serves as a substitute for experts for consulting media. In its manufacture, the system uses the backward chaining method for laptop damage data. The results of this study can detect laptop damage more quickly and precisely in helping users. With this system, it is hoped that it can help laptop users in overcoming the problem of laptop damage.